Developing a stress induction tool relevant to relationships in a health context - Kim, Youngmee; Carver, Charles S.; Hurwitz, Barry E. (Frontiers in Psychology, 2023)
Concerns pertaining to health and to problems in close relationships are both known to be major stressors, yet existing tools are inadequate to assess individual reactions to such stressors. Thus, we sought to develop and preliminarily validate a stress-inducing task for use in a laboratory setting that pertains to the sorts of health-related concerns people face in close relationships. Heterosexual dating couples (44 individuals: mean age 22) were randomized to be paired with their own partner or a stranger and to play a role of speaker or listener. Participants were asked to imagine a scenario in which one person is hit by a car (listener role) and the partner has no means to provide or seek out help for the victim (speaker role). The session consisted of baseline, speech preparation, stress task, and recovery phases. General linear modeling results revealed that the task induced stress, evidenced in cardiovascular activities and self-reported negative affect. Giving a brief speech about the stressful situation creates physiological and psychological strains, regardless of pairing with one’s own partner or stranger. Furthermore, caridovascular and negative affect reactivity to the STress Induction Tool for Close relationships and Health (STITCH) task tended to vary by individual characteristics that reflect one’s sensitivity to close relationship-and health-related stress. This tool is intended to be used for testing relationship theory driven phenomenon and longer-term implications of physiological and affective reactivities in the quality of life and health outcomes of those who experienced a medically stressful circumstance personally or in the family.